Evaluating KBSM forms four and five sports science in secondary schools in Malaysia / Wee Eng Hoe, Kee Kang Mea and Nadiah Diyana Tan Abdullah - Wee, Eng Hoe; Kee, Kang Mea; Tan Abdullah, Nadiah Diyana (Unit for Research and Intellect Application (UfoRIA), 2009)
This study was designed to evaluate the implementation of the Form 4 and 5 Sports Science Curriculum in the Malaysian schools. A questionnaire which was formulated by the researchers was administered to 94 Sports Science teachers in Malaysia. Majority of the Sports Science teachers were males and were below 40 years of age. Majority were trained in Sports Science and Physical Education. About half of the teachers were teaching between 5-14 years and majority taught 4-8 periods of Sport Science per week. Majority of the teachers have attended Sports Science related courses, Physical Education related courses and sports related courses. However only about 70% of the Sports Science teachers had attended Sports Science Orientation Course. Inadequate facilities is considered to be a very serious problem. Sports Science teachers felt that financial allocation is inadequate, teaching aids are scarce, reference books are inadequate and emphasized that they need a Sports Science text book and teachers' guide book. In term of teaching, male teachers and teachers with 3 years Sports Science experience are more capable in managing students and in conducting activities/experiments. However, they agreed that administrators consulted them before assigning them to teach but they failed to discuss factors affecting the teaching and learning of Sports Science. For further research, it is recommended that perceptions of students on Sports Science subject and its implementation should be undertaken.